1990
DOI: 10.1099/00221287-136-11-2155
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative and cytotoxic responses of human peripheral blood mononuclear cells to mannoprotein constituents of Candida albicans

Abstract: Two major proteoglycan constituents (designated F1 and F2) of the cell wall of Candida albicans were separated by ion-exchange chromatography from a crude carbohydrate-rich extract (GMP), and investigated for their chemical and molecular composition, antigenicity and immunomodulatory properties in cultures of human peripheral blood mononuclear cells (PBMC). Both fractions consisted predominantly of Periodic acidSchitf (PAS) and concanavalin A (Con A)-reactive material consisting of > 90 % mannose, 3-5% protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…In particular, Candida and Cryptococcus MPs were shown elsewhere to induce lymphoproliferation (19,23) and cytokine production (21,22,27). Previous data showed that interleukin-12 (IL-12) plays a pivotal role in induction of the Thelper type 1 (Th1) response against C. neoformans infection, this response being essential for protection (6).…”
mentioning
confidence: 99%
“…In particular, Candida and Cryptococcus MPs were shown elsewhere to induce lymphoproliferation (19,23) and cytokine production (21,22,27). Previous data showed that interleukin-12 (IL-12) plays a pivotal role in induction of the Thelper type 1 (Th1) response against C. neoformans infection, this response being essential for protection (6).…”
mentioning
confidence: 99%
“…Despite the increased awareness of the important role that CMI plays in the defense against this fungal pathogen (reviewed in references 1 and 38), very few CMI antigen targets for it have so far been identified. These include heat shock proteins, enolase, and a number of as yet uncharacterized mannoproteins, some with adhesin function (6,12,15,27,29,30,40).We have long been studying a 65-kDa mannoprotein (designated MP65) which is present in both the structural and secretory mannoprotein material and which is recognized by T cells of peripheral blood of practically all healthy individuals (quasiuniversal antigen) (20,(42)(43)(44). In mice immunized with whole fungal cells or MP65-rich mannoprotein extract (MP-F2) (44), a vigorous lymphoproliferative response with a prevalent T-helper type 1 (Th1) cytokine pattern was elicited in in vitro MP65-stimulated lymphomonocyte cultures (31).…”
mentioning
confidence: 99%
“…We have long been studying a 65-kDa mannoprotein (designated MP65) which is present in both the structural and secretory mannoprotein material and which is recognized by T cells of peripheral blood of practically all healthy individuals (quasiuniversal antigen) (20,(42)(43)(44). In mice immunized with whole fungal cells or MP65-rich mannoprotein extract (MP-F2) (44), a vigorous lymphoproliferative response with a prevalent T-helper type 1 (Th1) cytokine pattern was elicited in in vitro MP65-stimulated lymphomonocyte cultures (31).…”
mentioning
confidence: 99%
“…Moreover, and perhaps more importantly, this mannoproteic constituent is expressed on the cell surface of C. albicans [13], a microorganism endowed with a high rate of colonization and invasion of mucosal sites in AIDS patients. In HIV + subjects, the intense C. albicans colonization and spread of infection in several mucosal sites may lead to strong activation of PMNL, in addition to other cytokineproducing cells, such as macrophages and Candida-responsive lymphocytes [10,11]. Thus, activated PMNL should be considered as possible in vivo contributors to determine the state of chronic immune activation typical of the HIV + subject.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective PMNL activators is a mannoprotein fraction of Candida albicans, designated MP-F2 [9][10][11], which induces lactoferrin secretion and causes growth inhibition of lactoferrin-sensitive microorganisms [8,12]. Candida albicans itself is a human commensal and opportunistic pathogen which causes very frequent, extensive infections of the mucosa (oropharingeal, oesophageal, vaginal) in subjects infected by HIV [13,15].…”
Section: Introductionmentioning
confidence: 99%